Incidence of syphilis in Greenland 2010–2014: The beginning of a new epidemic? - Albertsen, Nadja (Int J Circumpolar Health, 2015)
OBJECTIVE: To estimate the incidence of syphilis from 2010 to 2014 and to assess whether contact tracing has been performed. STUDY DESIGN: Observational cross-sectional study. METHOD: Data on reported cases were collected from the national register of the chief medical officer in Greenland. Unreported cases were found by searching the electronic medical record system for patients who had received an electronic prescription of benzathine penicillin, doxycycline or tetracycline. Medical records were reviewed to verify the diagnosis of syphilis and to evaluate if contact tracing had been performed. RESULTS: Ninety-four cases of syphilis (51 males and 43 females) with a median age of 27 years (20–40) were included. The incidence of syphilis in Greenland has increased from zero cases in 2010 to 95.7 per 100,000 inhabitants in 2014 affecting mainly young people. Contact tracing was performed in 80.9% (76/94) of the cases. CONCLUSION: Syphilis has re-occurred in Greenland and a new epidemic may be underway. Sustained awareness of treatment, contact tracing, monitoring and preventive initiatives are desirable.